2018
DOI: 10.3390/su10072372
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Sand and Dust Storms (SDS) Intensity in China Based on Meteorological Data

Abstract: Sand and dust storms (SDS) are global phenomena that significantly impact the socio-economy, human health, and the environment. The characterization of SDS intensity is a fundamental aspect of SDS issues and studies. In this study, a sand and dust storms index (SDSI) is developed to characterize SDS intensity by addressing the potential impacts of sand and dust storms on sensitive elements. Compared with other indices, SDSI includes four SDS-related components: SDS frequency, SDS visibility, SDS duration, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…It is worth noting that the clear sky condition was not included since it corresponds to unobstructed horizontal visibility that extends beyond 10 km. Furthermore, it has been statistically inferred that for a span of two decades, the lowest storm-erupting wind speed was 5 m/s [36], which validates the 4th tabulated environment condition since the reported wind velocity was 7.3 m/s. Besides, with visibility of 0.56 km, it shows exceptional conformity to the CMA's specified visibility projections (0 ≤ visibility ≤ 1 km) for SDS events.…”
Section: Evaluating the Proposed Visibility Calculation Methodssupporting
confidence: 71%
“…It is worth noting that the clear sky condition was not included since it corresponds to unobstructed horizontal visibility that extends beyond 10 km. Furthermore, it has been statistically inferred that for a span of two decades, the lowest storm-erupting wind speed was 5 m/s [36], which validates the 4th tabulated environment condition since the reported wind velocity was 7.3 m/s. Besides, with visibility of 0.56 km, it shows exceptional conformity to the CMA's specified visibility projections (0 ≤ visibility ≤ 1 km) for SDS events.…”
Section: Evaluating the Proposed Visibility Calculation Methodssupporting
confidence: 71%
“…Al-Dousari et al [46] identified eight major trajectories of the major dust storms that originate in the Middle East region (and classified according to size of particles) using remote sensing from NOAA AVHRR, MODIS and TOMS (Total Ozone Mapping Spectrometer) as well as on-site sampling using dust traps and laboratory techniques similar to the ones mentioned above. Cao et al [53] use meteorological data to study dust storm events and generate a sand dust storm index at several locations all across China and specifically in the Tree-North Forest Shelterbelt Program region and identified the origin of the sand at these locations.…”
Section: Discussionmentioning
confidence: 99%
“…Various variables (such as visibility, concentration, and aerosol optical depth (AOD)) characterize a dust event, and authors like [ 19 , 20 ] have proposed some indices to gauge intensity. However, not all variables possess sufficiently long time series for robust conclusions.…”
Section: Introductionmentioning
confidence: 99%